Some duality relations for local splines - Dronov, S. G.; Ligun, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain duality relations for local periodic cubic and parabolic splines of minimal defect and establish some of their corollaries.